Phraseological units: persuasion and translation - Díez Arroyo, Marisa (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2009)
This paper explores the persuasive power of phraseological units (PUs) in cosmetics leaflets written either in English or French, together with their translation into French or English, respectively, as well as into Spanish. The approach rests upon, firstly, the concept of genre, determined, in agreement with Swales (1990), on the basis of the purpose of the text. Cosmetics leaflets are argued to be a manifestation of advertising. Hence, their ultimate aim is to persuade the (potential) buyer about the benefits of the product. Secondly, the occurrence of the phraseological units in this type of genre has important consequences for rhetoric and stylistics. Thirdly, we deal with the definition of phraseological units and their relation to metaphor, which will permit us to study how persuasion is achieved through this particular text type. Finally, by comparing the source text with its translation into two other languages, we analyse whether the translator has grasped the stylistic effect of the phraseological units and has succeeded in conveying a similar value in the target language text.